Rethinking the Traditional Classroom: Transitioning to Hybrid Teaching - Ritchey, Lynn (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
In the past few years, many faculty members have developed on-line or distance learning courses and some students have gravitated to this means of learning. However, available research shows this type of learning is not for everyone. I was once a corporate trainer and oversaw online or computer based training. I discovered that only 7% of the employees who signed up for a computer-based training completed the course. Online courses may be appropriate for only motivated high achievers. Unfortunately, this leaves the majority of students who try online and distance learning courses frustrated and often with an incomplete in the course.